Enhancing Cognitive Learning Outcomes and Retention through Reflective Learning Journals: Evidence from Senior High School Students - Nurhidayah, Nurhidayah; Indrawati, Nenny; Sumanik, Novike Bela (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
Reflective learning journals are an active learning strategy designed to enhance metacognition and knowledge consolidation. This quasi-experimental study investigated the effect of reflective learning journals on cognitive learning outcomes and knowledge retention among 64 Grade XI science students in Indonesia. A pretest-posttest-retest control group design was employed. The experimental group (n=32) used structured learning journals with teacher feedback, while the control group (n=32) received conventional instruction. Cognitive learning outcomes and retention were measured using validated multiple-choice tests. Results indicated that the experimental group significantly outperformed the control group on both the posttest (M=75.63 vs. M=59.84) and the retention test (M=76.25 vs. M=60.94). MANOVA confirmed a significant multivariate effect of the intervention (p < .001). The findings suggest that integrating reflective learning journals with feedback is an effective pedagogical strategy for enhancing both immediate learning and long-term retention in high school biology.”